Analisis Kinerja Kualitas Pelayanan, Kepercayaan dan Layanan Keuangan Digital (Mobile Banking) Terhadap Kepuasan Nasabah Bank Konvensional di Surakarta - Nova Caroline; Banu Witono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the performance of Service Quality, Trust and digital mobile bangking on customer satisfaction of conventional banks in Surakarta. The type of research used in this study is quantitative research. The population in this study is a conventional bank located in surakarta without any requirements. In this study, researchers used Convenience Sampling technique. In this study , researchers chose 3 conventional banks as a sample of research, namely BRI, BCA and MANDIRI. Data collection using the method of distributing questionnaires using google form. This study used multiple regression model. The results showed that the quality of Service, Trust and mobile bangking affect the customer satisfaction of conventional banks in Surakarta.